Method of ensuring noise resistance for measurement of microcontrollers medium energy consumption - Кочан, В. В. (Science-based technologies, 2020)
The paper considers the development of a system for measuring average power consumption of the microcontroller and microprocessor (hereinafter MC) during execution of instructions, commands, a set of commands, programs and their fragments. This system is based on the known system for measuring the instantaneous and average energy consumption of the MC, which ensures the operation of the MC in the normal operation mode with the presence of the capacitor in the power supply leg as well as the powering the MC from the current source. This allows calculating the current consumption of the MC using Kirchhoff's current law. Changes of the voltage across the capacitor in the power supply leg of the MC allow estimating the energy balance in the supply leg and energy consumption by the MC. However, the measurement error of the described system increases due to normal-mode noise induced by 220 V power network. The goal of the paper is to improve the described system by synchronizing the measurement process with zero crossing of the sinusoidal network voltage on conditions that both the voltage changes across the capacitor and their integral do not exceed the permissible levels. It is also necessary not to exceed the minimum and maximum durations of the measurement cycle as well as the deviation from the zero crossing for voltage of the power network. These conditions ensure high accuracy of measurements of average power consumption under influence of normal mode noise induced by the power supply network. The paper also presents the circuits that fulfill these conditions. The results of the study of the power consumption of the MC by the developed system, due to its high accuracy and noise immunity, allows optimizing the software of the MC for power consumption and, thus, extend the lifespan of autonomous devices without recharging the batteries.